(3OQGSI GdLOhi GdGbJUGOjI h Jbjje GdeTQhYGJ GdGSJKeGQjI (B/s - (3SdGe, CSGeI YRejs; (3ehSi, TbjQj fhQj s ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2011)
(3GdJYQja HOQGSGJ GdLOhi GdGbJUGOjI (B: (3GdeTQhY GdGSJKeGQj h YfGUQg h CfhGY GdeTGQjY GdGSJKeGQjI , GdJYQja, GdLOhi GdJShjbjI , GdLOhi GdafjI , GdLOhi GdeGdjI , GdLOhi GdGLJeGYjI ddeTQhY , bjGS eNGWQ GdGbJQGMGJ GdGSJKeGQjI h GOGQI GdGSJKeGQGJ GdeDbJI , Jbjje GdeTGQjY GdbGFeI h eYGdLI GdeTGQjY GdaGTdI , MGdGJ YedjI dOQGSI Lhi ChdjI eY hLhO CSFdI h JeGQjf aj fgGjI cd aUds
Keywords: (3GdESJKeGQs; (3GdeTQhYGJs; (3OQGSI GdLOhis